On the population, physical decay and orbital distribution of Jupiter family comets: numerical simulations - Di Sisto, Romina Paula (2009)
We study the Jupiter family comet (JFC) population assumed to come from the Scattered Disk and transferred to the Jupiter’s zone through gravitational interactions with the Jovian planets. We shall define as JFCs those with orbital periods P<20yr and Tisserand parameters in the range 2<T≲3.1, while those comets coming from the same source, but that do not fulfill the previous criteria (mainly because they have periods P>20yr) will be called ‘non-JFCs’. We performed a series of numerical simulations of fictitious comets with a purely dynamical model and also with a more complete dynamical-physical model that includes besides nongravitational forces, sublimation and splitting mechanisms. With the dynamical model, we obtain a poor match between the computed distributions of orbital elements and the observed ones. However with the inclusion of physical effects in the complete model we are able to obtain good fits to observations. The best fits are attained with four splitting models with a relative weak dependence on q, and a mass loss in every splitting event that is less when the frequency is high and vice versa. The mean lifetime of JFCs with radii R>1km and q<1.5AU is found to be of about 150-200 revolutions (˜103yr). The total population of JFCs with radii R>1km within Jupiter’s zone is found to be of 450±50. Yet, the population of non-JFCs with radii R>1km in Jupiter-crossing orbits may be ˜4 times greater, thus leading to a whole population of JFCs + non-JFCs of ˜2250±250. Most of these comets have perihelia close to Jupiter’s orbit. On the other hand, very few non-JFCs reach the Earth’s vicinity (perihelion distances q≲2AU) which gives additional support to the idea that JFCs and Halley-type comets have different dynamical origins. Our model allows us to define the zones of the orbital element space in which we would expect to find a large number of JFCs. This is the first time, to our knowledge, that a physico-dynamical model is presented that includes sublimation and different splitting laws. Our work helps to understand the role played by these erosion effects in the distribution of the orbital elements and lifetimes of JFCs.